Digital Health Literacy and Patient Experience in Digital Health Services: A Systematic Review of Engagement, Satisfaction, and Loyalty-Related Outcomes - C. Lily Riana; Nur Afifah; Mustaruddin Mustaruddin; Titik Rosnani (JURNAL ECONOMINA, 2026)
Background: Digital health services (e.g., telemedicine, patient portals, and mobile health apps) are increasingly embedded in care delivery, making digital health literacy (DHL/eHealth literacy) a plausible determinant of service outcomes. Objective: This systematic literature review (SLR) synthesises empirical evidence on the association between DHL/eHL and patient-reported outcomes that are central to service management: digital patient experience, patient satisfaction, and loyalty-related outcomes (intention to use and continuance intention). Methods: A PEO-informed search was performed in Scopus using a structured query combining DHL/eHL terms, service outcomes, and digital service contexts. Primary empirical studies measuring DHL/eHL and reporting relevant outcomes among patients/end-users were eligible; non-empirical publications and studies without explicit DHL/eHL measurement were excluded. Study quality was appraised using the Joanna Briggs Institute checklist for analytical cross-sectional studies. A narrative synthesis was conducted due to heterogeneity. Results: From 35 retrieved records, four cross-sectional studies (2020-2025) met inclusion and quality thresholds. Across mHealth apps, clinical digital services, online consultation and social-media-based consultation, higher DHL/eHL was consistently associated with stronger intention/continuance and higher satisfaction. Reported mechanisms involved technology acceptance perceptions (usefulness and ease of use), trust/privacy, digital information accessibility and attitudes, and patient-provider communication/empowerment processes. Conclusion: DHL/eHL appears to function as a foundational capability for positive digital service outcomes, but the evidence base is small and dominated by cross-sectional self-report designs. Longitudinal and intervention studies and more standardised outcome measurement are priorities for advancing theory and informing DHL-responsive service design.